Characteristics of wall heat transfer from impinging diesel spray flame in low oxygen concentration ambient. Issue 1 (January 2021) - Mahmud, R; Nishida, K; Ogata, Y; Kurisu, T
Abstract: The objective of this study is to obtain an enhanced understanding of the effect of diesel spray/flame impingement on transient heat flux to the wall. By using a constant volume vessel under engine-like condition, surface heat flux of the wall at spray/flame impingement was measured with three thin film thermocouple heat flux sensors. Fuel was injected using a single-hole injector with a 0.133 mm diameter nozzle. In order to investigate the relation between diesel flame and wall heat loss, two color-method was applied to observe flame temperature distribution. 21 % and 16 % as the various oxygen concentration were investigated at each injection pressure of pressure 80, 120, and 180 MPa. The results showed that the lower oxygen concentration was generated heat loss regardless of injection pressures. The lower flame temperature and flame contact area and period were influence factor on heat loss on the wall. Furthermore, the relation between Nusselt number ( Nu ) and Reynolds number ( Re ) were also investigated to understand the heat transfer phenomena in diesel engines.